Intervenções em linguagem escrita: Uma revisão da literatura com vistas à redução dos transtornos funcionais de aprendizagem - Oliveira, Jáima Pinheiro de [UNESP]; Braga, Tania Moron Saes [UNESP] (FapUNIFESP (SciELO), 2011)
The importance reading and writing and being able to use these skills in a variety of situations is an absolute reality. In our society in which reading and writing are widely used, Brazil still faces severe problems with literacy, as revealed in literacy statistics and in the large number of students with learning disabilities. Thus, our text aims to present a survey of the research that focuses on intervention programs highlighting the needs of this group, with special attention on the use of narrative or storytelling. Specific criteria were established, the main one being the period of the publications (2000 to 2010). The results of the analysis of 15 texts showed that intervention is the most neglected area. International literature presents concerns related to scientific rigor or greater control of variables related to ongoing programs, as well as measures for generalizing the effective use of these programs, within verbal communities, with special focus on schools. Our revision enabled us to conclude that, even though production on written language is large, international literature is much more expressive with reference to intervention programs. Furthermore, in both national and international literature, production concerning the understanding of written language processes of acquisition and development prevails.
Intervention in written language: A review of the literature focusing on reducing functional learning disorders
Keywords: Behavior Intervention; Inclusive Education; Learning Difficulties; Production of Knowledge; Written Language